Handbook on Economics of Discrimination and Affirmative Action - Deshpande, Ashwini (Springer Nature Singapore, 2023)
Dimensions of Discrimination -- Insights from Social Psychology -- Intersectionality and Discrimination -- Methodological Approaches to Understanding Discrimination: Decomposition Methods -- Methodological Approaches to Understanding Discrimination: Field Experiments.
Keywords: Aufsatzsammlung